In Vitro Comparison of Antibacterial and Antibiofilm Activities of Selected Fluoroquinolones against Pseudomonas aeruginosa and Methicillin-Resistant Staphylococcus aureus - Masadeh, Majed M. (Pathogens, 2019)
An in vitro overview of the inhibitory effects of selected fluoroquinolones against planktonic and biofilm cells of the methicillin-resistant Staphylococcus aureus (MRSA) strain American type culture collection (ATCC) 43300 and the Pseudomonas aeruginosa strain ATCC 27853 was carried out. Biofilm cells of both strains were less susceptible to the selected antibiotics than their planktonic counterparts. In addition, certain antibiotics were more effective against biofilm cells, while others performed better on the planktonic cells. Against P. aeruginosa, ciprofloxacin was the most potent on both planktonic and biofilm cells, whereas ofloxacin was the least potent on both biofilm and planktonic cells. Moxifloxacin and gatifloxacin were the most potent against both planktonic and biofilm MRSA bacteria, however, not in the same order of activity. Norfloxacin was the least active when tested against both planktonic and biofilm cells. The results of this work are expected to provide insight into the efficacy of various fluoroquinolones against MRSA and Pseudomonas aeruginosa biofilms. This study could form the basis for future clinical studies that could recommend special guidelines for the management of infections that are likely to involve bacteria in their biofilm state.